2012
DOI: 10.1038/ng.2370
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies NMNAT1 mutations as a cause of Leber congenital amaurosis

Abstract: Leber congenital amaurosis (LCA) is an autosomal recessive retinal dystrophy that manifests with genetic heterogeneity. We sequenced the exome of an individual with LCA and identified nonsense (c.507G>A, p.Trp169*) and missense (c.769G>A, p.Glu257Lys) mutations in NMNAT1, which encodes an enzyme in the nicotinamide adenine dinucleotide (NAD) biosynthesis pathway implicated in protection against axonal degeneration. We also found NMNAT1 mutations in ten other individuals with LCA, all of whom carry the p.Glu257… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 14 publications
2
97
0
Order By: Relevance
“…RPE cannot survive long-term deficiency of NAD + (37, 38), and a mutation in nicotinamide nucleotide adenylyltransferase 1 (NMNAT1), the enzyme that converts NMN into NAD + , causes severe retinal degeneration in humans (39)(40)(41). We have shown that, when oxidative stress is excessive, PARP depletes NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…RPE cannot survive long-term deficiency of NAD + (37, 38), and a mutation in nicotinamide nucleotide adenylyltransferase 1 (NMNAT1), the enzyme that converts NMN into NAD + , causes severe retinal degeneration in humans (39)(40)(41). We have shown that, when oxidative stress is excessive, PARP depletes NAD + .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, beyond their neuronal roles, Nmnats also have obligate roles in NAD + metabolism and multiple cellular processes across species (Zhai et al, 2009;Lin et al, 2010). Very recent reports show Nmnat1 mutations cause Leber congenital amaurosis (LCA), highlighting its importance in retinal degenerative diseases in humans (Chiang et al, 2012;Falk et al, 2012;Koenekoop et al, 2012;Perrault et al, 2012).…”
Section: Wldmentioning
confidence: 99%
“…GUCY2D, NMNAT1, RDH12, RPGRIP1, and CRB1) (1). A 10-centimorgan region on 1p36 was identified as LCA9 locus in a Pakistani family (2) and further analysis identified NMNAT1 mutations in families with LCA, most of which had associated macular atrophy (3)(4)(5)(6). Almost all of these patients harbored compound heterozygote mutations, with the most common being a missense E257K mutation (3)(4)(5)(6).…”
Section: Leber Congenital Amaurosis (Lca)mentioning
confidence: 99%
“…A 10-centimorgan region on 1p36 was identified as LCA9 locus in a Pakistani family (2) and further analysis identified NMNAT1 mutations in families with LCA, most of which had associated macular atrophy (3)(4)(5)(6). Almost all of these patients harbored compound heterozygote mutations, with the most common being a missense E257K mutation (3)(4)(5)(6). A new study reports that individuals with a homozygous E257K mutation in one family did not have ocular abnormalities, suggesting this is a hypomorphic mutation with incomplete penetrance (7).…”
Section: Leber Congenital Amaurosis (Lca)mentioning
confidence: 99%
See 1 more Smart Citation